Upaya Meningkatkan Prestasi Belajar IPS dengan Model Science Technology Society Peserta Didik Kelas VIII B SMP Trisula Ngluwar Kabupaten Magelang - Miftachul Janah; Salamah Salamah (Proceedings Series on Social Sciences & Humanities, 2022)
This study aims to improve social studies learning achievement with the Science Technology Society model for Class VIII B students at Trisula Ngluwar Middle School, Magelang Regency. This research is a classroom action research with the research subjects are students of class VIII B SMP Trisula Ngluwar totaling 22 students consisting of 14 male students and 8 female students. This research was conducted in two cycles, the first cycle consisted of two meetings and the second cycle consisted of two meetings. At the end of each cycle an evaluation is carried out. Data collection techniques using observation, evaluation of learning achievement results and documentation. The data analysis technique in this research is quantitative descriptive analysis. The results showed that the learning achievement of class VIII B SMP Trisula Ngluwar in social studies learning could be improved by using the Science Technology Society model. Social studies learning achievement during the pre-cycle students obtained an average of 53.11 with a percentage of 36.36% as many as 8 students got the minimum KKM score and 14 students still did not reach the KKM. It increased in the first cycle of student achievement to an average of 70.13 with a percentage of 59.09% as many as 13 students got the minimum KKM score and 9 children still did not reach the KKM. Increased in the second cycle of student achievement to an average of 78.13 with a percentage of 86.36% as many as 19 students get a minimum score of KKM and 3 students who have not reached the KKM.